Long term average spectrum of Singaporean English speakers and the influence of ethnicity on voice quality - Phua, Ryan Rui Kiat (Nanyang Technological University, 2022)
Long-term average spectrum (LTAS) illustrates and paints a clear view of the mean spectral characteristics of one's voice. Prior research has shown how LTAS can be used to study the effects of age, sex, speech clarity and language variety on voice quality. Research has predominantly been conducted on the English varieties (American, British, Australian), with little research conducted on Singapore English. Research on the effects of ethnicity has also been primarily focused on the prosodic and segmental components of speech, where ethnicity has proven to be detectable and distinguishable by participants. This study details the observation of the normative Singapore English speaker's LTAS, specifically within the young adult category. Additionally, this study will also utilise Principal Component Analysis (PCA) as a method of analysis to observe the possibility of the influence of ethnicity on LTAS. Results from mean LTAS comparisons between ethnicity as well as PCA reveal that the influence in ethnicity is either not present or undetectable in the LTAS of Singaporean English speakers. Future studies could attempt modifying the experimental method or increase the scale of participants gathered in order to verify that ethnicity only influences the prosodic and segmental strands of speech.